Prediction scores for risk of allograft loss in patients receiving kidney transplants: nil satis nisi optimum - Montero, Nuria (Clin Kidney J, 2020)
Long-term graft survival is the main concern of kidney transplantation. Some strategies have been tested to predict graft survival using estimated glomerular filtration rate or proteinuria at different time points, histologic assessment, non-invasive biomarkers or even machine-learning methods. However, the 'magical formulae' for allograft survival prediction does not exist yet.